Exercise effects on muscle stem cells - Jurdana, Mihaela (Annales kinesiologiae (Koper), 2017)
Satellite cells are skeletal muscle stem cells that facilitate muscle repair and regeneration after "damage" which occurs after physiological stimuli: exercise, post-training micro-injuries and electrical stimulation. Exercise stimuli lead to activation and proliferation of these cells from their quiescent state, therefore, increasing cell numbers having the potential to provide additional myonuclei to their parent muscle fibre or return to a quiescent state. Different exercise modalities are the focus of numerous studies on satellite cells activation. An increase in muscle activity augments satellite cells proliferation as well as skeletal muscle mass and function, both in young and elderly. This review provides an updated view of the contribution of skeletal muscle satellite cells in regulating skeletal muscle mass and the efficiency of the exercise intervention to attenuate the decline in muscle mass.
Keywords: acute exercises; akutna vadba; chronic exercises; kronična vadba; micro damage; mikro poškodbe; mišična regeneracija; muscle regeneration; satelitske celice; satellite cells